Acetylsalicylic acid decreases clotting in combination with enoxaparin during haemodialysis in vitro. Issue 3 (23rd July 2018) - Samaha, Eslam; Schwameis, Michael; Schranz, Sabine; Watschinger, Bruno; Buchmüller, Anja; Jilma, Bernd
Abstract: Background: Anticoagulation is a cornerstone in haemodialysis (HD) therapy to avoid clotting of blood when it comes into contact with the dialysis membrane. Although heparins are usually administered as anticoagulants, they are not always sufficient to maintain adequate HD. We investigated the additional effect of acetylsalicylic acid compared with standard anticoagulation on maintaining adequate flow properties during HD in vitro . Methods: We collected blood from 42 healthy volunteers, between 18 and 60 years of age, into bags filled with 1, 1.5 or 2 mg enoxaparin, with (treatment group) or without (control group) 100 mg of aspirin. Blood was evaluated before, during and at the end of each experiment to determine coagulation parameters, whole blood aggregation and thromboelastogram measurements. Transmembrane pressure was recorded as indirect estimate of dialysis patency. The primary endpoint was time to filter clotting. Results: Addition of acetylsalicylic acid significantly prolonged the time to circuit clotting from 120 (105–150) min to >180 min (120–180) min (P = 0.047) and allowed lowering the enoxaparin concentration from 2 mg per circuit to 1 mg without an increase in clotting. Furthermore, it reduced the transmembrane pressure from 46 to 4 mmHg (P < 0.001) after 4 h of dialysis. Acetylsalicylic acid better preserved the platelet count (128 versus 116 × 10E9/L, P = 0.01) and improved platelet aggregation at the end of the dialysis procedure. Conclusion: Adding acetylsalicylic acid to HD circuits lowered the transmembrane pressure, better preserved platelet function and prolonged the time to circuit clotting, which in sum increases haemodialyser performance and may facilitate a more effective HD.